The Cham Bani of Vietnam (American Journal of Islam and Society, 2006)
Based on 1989 statistics, approximately 131,282 Cham live in Vietnam.They are the descendents of Champa, an Indian-Hindu kingdom that, centurieslater, was heavily influenced by Arabic-Islamic culture. Buddhismalso made its way into Champa, but was confined to the royal circle duringthe reign of King Indravarman II (c. 896-905). Historically, the Cham weredivided along religious lines: Hindu and Muslim. The Muslim population issubdivided further between the Cham Banis and the mainstream (Sunni)Cham Islam. The Cham population is concentrated mainly in the lowermiddleand southern parts of Vietnam. In the middle part, they live scatteredin the Phan Rang and Phan Ri regions. In the southern and southwesternparts, they live in Tay Ninh, Chau Doc, An Giang, Ho Chi Minh City, LongKhanh, and Binh Phuoc cities. The Cham Banis and Cham Hindus onlyreside in Phan Rang and Phan Ri. There, the Cham Banis make up about onehalfof the Cham population, while the remaining half is Cham Hindu. However,in the south and southwest, all of them follow mainstream Islam ...